PEDAGOGICAL SHIFTS IN SCIENCE CLASSROOMS: INSIGHTS FROM MASTER OF TEACHING CANDIDATES IN BRUNEI DARUSSALAM - Hardimah Hj Md Said (Seminar Nasional Pendidikan IPA Ke III Tahun 2025, 2025)
Science education is increasingly required to respond to the demands of 21st-century learning, rapid technological advancement, and the need for inclusive and meaningful learning experiences. This paper examines pedagogical shifts in secondary science classrooms through insights drawn from Master of Teaching (MTeach) science candidates in Brunei Darussalam. Using reflective accounts grounded in sustained school-based practice, the paper highlights shifts from teacher-centred instruction toward student-centred, inquiry-driven, and adaptive pedagogies. It further explores the growing emphasis on conceptual understanding, the purposeful integration of digital and artificial intelligence (AI) tools, and the ethical considerations that accompany their use. The paper argues that reflective practice, mentorship, and professional support are central to sustaining pedagogical transformation and shaping future-ready science classrooms.